Effectiveness of Using Augmented Reality for Training in the Medical Professions: Meta-analysis - Baashar, Y. (JMIR Publications Inc., 2022)
Background: Augmented reality (AR) is an interactive technology that uses persuasive digital data and real-world surroundings to expand the user's reality, wherein objects are produced by various computer applications. It constitutes a novel advancement in medical care, education, and training. Objective: The aim of this work was to assess how effective AR is in training medical students when compared to other educational methods in terms of skills, knowledge, confidence, performance time, and satisfaction. Methods: We performed a meta-analysis on the effectiveness of AR in medical training that was constructed by using the Cochrane methodology. A web-based literature search was performed by using the Cochrane Library, Web of Science, PubMed, and Embase databases to find studies that recorded the effect of AR in medical training up to April 2021. The quality of the selected studies was assessed by following the Cochrane criteria for risk of bias evaluations. Results: In total, 13 studies with a total of 654 participants were included in the meta-analysis. The findings showed that using AR in training can improve participants' performance time (I2=99.9; P < .001), confidence (I2=97.7; P = .02), and satisfaction (I2=99.8; P = .006) more than what occurs under control conditions. Further, AR did not have any effect on the participants' knowledge (I2=99.4; P = .90) and skills (I2=97.5; P = .10). The meta-regression plot shows that there has been an increase in the number of articles discussing AR over the years and that there is no publication bias in the studies used for the meta-analysis. Conclusions: The findings of this work suggest that AR can effectively improve performance time, satisfaction, and confidence in medical training but is not very effective in areas such as knowledge and skill. Therefore, more AR technologies should be implemented in the field of medical training and education. However, to confirm these findings, more meticulous research with more participants is needed. Â© Yahia Baashar, Gamal Alkawsi, Wan Nooraishya Wan Ahmad, Hitham Alhussian, Ayed Alwadain, Luiz Fernando Capretz, Areej Babiker, Adnan Alghail. Originally published in JMIR Serious Games (https://games.jmir.org), 05.07.2022.